Information System for Monitoring the Development of Children With Special Needs - Aman, Andryanto; Utami, Listia; Aras, Muhammad Khaidir Alif; Kasmi, Mauli (Ceddi Journal of Education, 2022)
The supervision of students, particularly those with special needs, is predominantly carried out by schools. However, due to the busy schedules of many parents, continuous monitoring of their children's development at school is often limited. Typically, parents only receive information about their child's learning progress once a semester, during the distribution of report cards. This delayed communication highlights the need for a more efficient and timely system at SLB C YPPLB 2 Makassar to provide parents with ongoing updates about their child's development. This study aims to design and implement an information system for monitoring the development of children with special needs at SLB C YPPLB 2 Makassar City. The system is intended to facilitate direct and real-time communication between the school and parents, enabling parents to monitor their child's progress actively. The research methodology involved data collection through observation, interviews, and documentation. The system was developed using a structured approach, which included Needs Analysis, System Design, Implementation and Unit Testing, System Integration/Testing, and System Maintenance. BlackBox testing was employed to evaluate the system's functionality. The findings of this study indicate that the development monitoring system for children with special needs at SLB C YPPLB 2 Makassar City is highly effective, with a usability score of 90%, reflecting a strong positive response from users. This research contributes to the body of knowledge by demonstrating how an information system can bridge the communication gap between schools and parents of children with special needs, fostering more proactive and informed parental involvement in the educational process.